MULTI-SENSORY ACTIVITY IN EARLY CHILDHOOD EDUCATION: TEACHERS’ PERCEPTION ON THE IMPORTANCE OF ACTIVITY IMPLEMENTATION - Syazwani Aniyah Manja; Abdul Halim Masnan; Mazlina Che Mustafa; Norazilawati Abdullah (Jurnal Penyelidikan Sains Sosial, 2022)
The purpose of this study was to survey teachers’ perceptions on the importance of implementing multi-sensory activities to children. Perception among early childhood education teachers is seen based on teachers’ general perceptions on the importance of multi-sensory activities in early childhood education and teachers’ reaction toward the importance of implementation according to the type of multi-sensory activities. This study is a survey study using a questionnaire by Goodwin (2008) about Sensory Experiences in the Early Childhood Classroom: Teachers’ Use of Activities, Perceptions of the Importance of Activities, and Barriers to Implementation. Thus the respondents involved in this study are teachers of early childhood education in Proton City Area, Muallim District, Perak. The researcher chooses to use purposeful sampling and the total number of respondents involved is 30 teachers. The findings of the study found that a total number of 27 respondents is (90%) agreed on the importance of multi-sensory activities in early childhood education. The highest score of percentages for teachers’ perceptions toward the importance of implementation according to the type of multi-sensory activities, a total of 26 participants (86.7%) agreed with visual stimuli activity and art materials and activities implementation. Meanwhile the lowest score is contain of 21 participant (70%) that agreed with the implementation of multi-sensory activities through Outdoor Play. Although there are high and low percentage scores but it is still seen as important in the implementation of multi-sensory activity in early childhood education.